Case Report: Laboratory detection of a thrombotic tendency in a family with hypodysfibrinogenemia and a novel FGG mutation - Monard, Amaury; Castoldi, Elisabetta; De Simone, Ilaria; Wichapong, Kanin; van Duijl, Tirsa; van den Biggelaar, Maartje; Spada, Stefano; van Doorn, William; Hellenbrand, Dave; van der Meijden, Paola; Swieringa, Frauke; Stork, Alexander; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction Hypodysfibrinogenemia is a rare congenital fibrinogen disorder (CFD) which may induce thrombotic and bleeding events. Therefore, patient management needs careful evaluation. Routine coagulation tests are inadequate to predict the clinical phenotype. Clinical findings A 60-year-old woman with both bleeding and thrombotic complications and her two daughters were referred to our center for genotypic and phenotypic analysis of a CFD. Diagnosis Conventional laboratory results led to the diagnosis of hypodysfibrinogenemia in all three subjects. They all carried the same heterozygous c.1124A>G mutation in FGG resulting in p.Tyr375Cys amino acid substitution, which was confirmed by protein variant analysis from plasma. In silico structure analysis predicted possible conformational and functional changes of the fibrinogen molecule. Thrombin generation indicated a hypercoagulable state confirmed by microfluidics that showed enhanced fibrin formation in both daughters, regardless of the coagulation trigger. Conclusion We report on a family with hypodysfibrinogenemia and a novel FGG heterozygous missense mutation, possibly leading to conformational changes or covalent dimerization. Thrombin generation and particularly microfluidic measurements disclosed a hypercoagulable state, which was not detected with routine coagulation tests, justifying a different patient management.